Influence of Higenamine on Exercise Performance of Recreational Female Athletes: A Randomized Double-Blinded Placebo-Controlled Trial - Rasic, Jelena S.; Ivanovic, Nevena DJ.; Andjelkovic, Marija S.; Nedeljkovic, Ivana P.; Nikolic, Ivan R.; Stojanovic, Sava D.; Ristic-Medic, Danijela K.; Takic, Marija M.; Djordjevic, Brizita I.; Dikic, Nenad V. (Frontiers in Psychology, 2021)
The aim of this study was to determine the ergogenic effects and the safety profile of a one-component higenamine supplement in female recreational athletes. Twelve recreational female basketball players (age 29-41 years, oxygen consumption (VO2max) > 30 ml˖kg-1˖min-1, with training >5 h˖wk-1) were randomized either to the higenamine group, or to the placebo group for 3 weeks. In order to determine ergogenic effects and safety profile of higenamine administration, we assessed the following variables before and after 3 weeks of supplementation: anthropometric parameters, resting metabolic rate (RMR), exercise testing variables, serum free fatty acids, blood pressure, enzyme activity, urea, lipid profile, and complete blood count. There were no differences between groups in anthropometric parameters, including Basal Metabolic Rate (BMR), RMR and body fat (p = 0.706 (Cohen`s d 0.223), p = 0.169 (Cohen`s d 0.857), p = 0.223 (Cohen`s d 0.750) respectively), free fatty acids (0.43±0.03 vs. 0.54±0.23, p = 0.206 (Cohen`s d 0.540)), neither significant differences in cardiopulmonary parameters after the intervention period. Furthermore, all measured outcome variables in the safety assessment were not significant, with values remaining stable during the intervention period for participants in both groups. This is the first study to document the effects and the safety profile of higenamine-based dietary supplements at a specified dose in female recreational athletes. Our data indicate that 21-day of supplementation with 75 mg higenamine would not result in improving cardiopulmonary exercise fitness and weight loss in female recreational athletes. Moreover, supplementation with 75 mg higenamine is safe and well-tolerated in younger recreational female athletes.